Chapter Quality Culture and Innovation in Higher Education - Togni, Fabio (Studies on Adult Learning and Education, 2023)
The Quality Assurance history and, in general, the building of quality concept have accompanied the humanity history. With the advent of the production systems of the second and third Industrialisations Movement, this meant strengthening the control of products and services. With the end of the last century, more and more quality has affected processes and organisations as a whole. Today, Total Quality Management models cover all sectors of goods and services. Thus, also education systems can have great benefits from the spread of a Quality Culture. The essay aims to trace the history of TQM and shows how it also concerns formal and informal training. It also wants to show how the introduction of Quality Assurance Systems helps to create positive effects at both the micro, meso, macro and mega levels.